The efficacy of different organic toxicants for selective elimination of predators and competitors in shrimp ponds - Rendon, Condrado G. (Miagao, Iloilo University of the Philippines, 1989)
This study was conducted at the BrackishwaterAqauculture Center (BAC), Leganes, Iloilo in February 1989 to find out the most effective organic toxicants and its effective lethal concentration. A Completely Randomized Design (CRD) with five treatments replicated three times was used in the study. The treatments were : Treatment A - "Tubli " (derris elliptica) ; B - Kayos (Dioscorea hispida) ; C - "Kasla" (Jatropha curcas) ; D - "Balanti" and E- Teaseed Cake (Camella sp.). Test animals were juvenile stages of T. mossambica, Glossogobius giurus, Poecillia sp. in polyculture with prawn. Five toxicants were applied simultaneously at the same concentration (20 ppm) following the treatment assignments.Results showed highly significant differences on the average percentage mortality of T. mossambica, G. G. giurus and and Poecillia sp. 1 hour after treatment of 20 ppm concentration of different toxicants.Depensatory mortality was observed with further increase in the concentration of teaseed, kasla, kayos and balanti but no significant differences were detected among them ; while, highly significant differences were found using 5, 10 and 15 ppm concentration of tubli (rotenone). Significant difference on the responses among species were observed based on their sinsitivity to toxicant relative to time of exposure ; while P. monodon was able to survive despite the increase on the concentrations of toxicants of time of exposure. .
Thesis (M.S. Fisheries) -- U.P. in the Visayas, October 1989.
Keywords: Organic toxicants; Shrimp ponds -- Organic toxicants